Educación para la paz. De la Constitución de 1991 a la Cátedra de la paz (2017)
The Colombian State established the Cátedra de la Paz (The Teaching of Peace) through Law 1732 of 2014 and its Regulatory Decree No. 1038 of 2015 within the framework of negotiations between the national government and the guerrilla forces of the Revolutionary Armed Forces of Colombia-Army of the People (FARC-EP). Its purpose was to enhance the involvement of the educational institutions of the country in a culture of peace in the context of negotiations. It clearly recognized the importance of education in this regard. This article aims to examine the national and international background that gave rise to the Cátedra, as well as to present the specific characteristics proposed for its implementation.